Basic Anthropological Concepts in the Macarian Corpus - Horyacha, Mariya (Vox Patrum, 2025)
The study analyzes the Macarian corpus of homilies from an anthropological perspective. As the author of these parenetic discourses relies on imagery rather than on terminology, his vocabulary is highly unsystematic. The aim of this article is to highlight the key anthropological concepts of the Macarian corpus and elucidate their meaning. The article consists of three parts: the first explores the Macarian use of anthropological terms such as body, soul, mind, and heart; the second focuses on the interrelation of these concepts, and the third considers the type of anthropology the author of the corpus developed. The analysis is based on the three main Greek collections: I (63 logoi), II (50 homilies), and III (43 discourses). It shows that the meanings of basic anthropological terms are blurred and cannot be determined by definition, but only through context. While their different aspects and nuances are revealed in their interplay, Macarian anthropology should be seen as a holistic one, in which basic anthropological terms usually imply the whole person. The study has also revealed the incomplete character of Macarian anthropology.